Pengembangan Hybrid App Arsip Ijazah dan SKHUN di SMK Pembangunan Bukittinggi - Khomarudin, Agus Nur; Novita, Rina; Aulia, Romy; Putri, Ega Evinda; Jamaluddin, Jamaluddin (Mahesa Research Institute, 2025)
The importance of fast, precise, and accurate information is highly essential for every institution or organization, particularly in archival management. SMK Pembangunan Bukittinggi is currently making continuous efforts to support the